Efectividad del gel de aloe vera ozonizado sobre la inhibición del crecimiento de Enterococcus faecalis - Castillo, David (Instituto Universitario de Innovación Ciencia y Tecnología Inudi Perú, 2022)
The objective of this study was to evaluate the effectiveness of ozonated Aloe Vera gel on the growth inhibition of Enterococcus faecalis according to application time. It was quasi-experimental, longitudinal and applicative. In a first instance, the Aloe Vera gel was collected. Once obtained, it was subjected to ozonation, for which the ozonation patterns of the water are taken. It was then applied to Enterococcus faecalis samples by means of diffusion disks and applied directly. The results were not very encouraging, showing inhibition halos no larger than 10 mm and 0 mm in diameter in several cases. For this reason, Aloe Vera gel was diluted in 70° alcohol and chloroform, obtaining better results. The sample consisted of Petri dishes incubated with Enterococcus faecalis, at a rate of 35 Petri dishes for each study group and application time. The gel was applied to the samples by diffusion of filter discs and by direct application. After several tests, the ozonated gel at 24 hours showed the best results with inhibition halos of 40-45 mm. In conclusion, the Ozonized Aloe Vera gel is a product that demonstrated a high effectiveness when applied on Enterococcus faecalis to extract its greatest properties, it is necessary to dilute them in 70° alcohol and chloroform, so it presents a high level on the bacteria.